Mechanisms and functional implications of the degradation of host RNA polymerase II in influenza virus infected cells. - Vreede, F; Chan, A; Sharps, J; Fodor, E (2010)
Influenza viruses induce a host shut off mechanism leading to the general inhibition of host gene expression in infected cells. Here, we report that the large subunit of host RNA polymerase II (Pol II) is degraded in infected cells and propose that this degradation is mediated by the viral RNA polymerase that associates with Pol II. We detect increased ubiquitylation of Pol II in infected cells and upon the expression of the viral RNA polymerase suggesting that the proteasome pathway plays a role in Pol II degradation. Furthermore, we find that expression of the viral RNA polymerase results in the inhibition of Pol II transcription. We propose that Pol II inhibition and degradation in influenza virus infected cells could represent a viral strategy to evade host antiviral defense mechanisms. Our results also suggest a mechanism for the temporal regulation of viral mRNA synthesis.